العدالة التنظيمية ودورها في إدارة ضغوط العمل لدى الموظفين الإداريين بجامعة القصيم - التويجري، هيلة منديل محمد (جامعة بيشة, 2021)
هدفت الدراسة لمعرفة دور العدالة التنظيمية في إدارة ضغوط العمل لدى الموظفين الإداريين بجامعة القصيم، وقد استخدمت المنهج الوصفي، وتكونت عينة الدراسة من الموظفين الإداريين بجامعة القصيم؛ وتم اختيار عينة البحث بالطريقة العشوائية البالغ قوامها (187) فردا، وخرجت الدراسة بعدة نتائج، أهمها: أن العدالة التنظيمية لها دور كبير في إدارة ضغوط العمل داخل المنظومة الإدارية بجامعة القصيم، وكان من أهم التوصيات تطبيق العدالة التنظيمية بكافة صورها (العدالة التوزيعية، العدالة الإجرائية، العدالة التفاعلية) داخل المنظومة الإدارية في التعليم الجامعي، والمضي قدما في انتهاج هذه السياسة لما لها من دور إيجابي في إدارة ضغوط العمل من خلال أبعادها (إدارة الصراعات، إدارة وفض المنازعات، تدعيم العلاقات) على الموظفين الإداريين
This study aimed at knowing the role of organizational justice in managing work stress for administrative personnel at Qassim university. The descriptive method was used from the administrative personnel at Qassim university. The research sample was used purposively of (187) individuals. The most important findings are that: Organizational justice has a great role in managing work pressures within the administrative system at Qassim University, and it also recommends the application of organizational justice, in all its forms (distributive justice, procedural justice, interactive justice) within the administrative system in university education, and moving forward with this policy because of its positive role in managing work stress through its dimensions (conflict management, managing and resolving disputes, strengthening relationships) on the administrative staff.
Keywords: الجامعات -- الموظفين الإداريين -- الأداء الوظيفي -- إدارة ضغوط العمل -- العدالة التنظيمية -- جامعة القصيم